1359Changes in work and health of Australians during the COVID-19 pandemic: a longitudinal cohort study. (2nd September 2021) - Griffiths, Daniel; Sheehan, Luke; Vreden, Caryn van; Petrie, Dennis; Whiteford, Peter; Sim, Malcolm; Collie, Alex
Abstract: Background: Following pandemic-related work loss, some people could return to work as restrictions eased, whilst localised lockdowns resulted in further loss of work. The long-term health effects of work loss within the pandemic remain unexplored, in addition to whether any health effects are persistent upon returning to work. Methods: A prospective longitudinal cohort study of 2603 Australians monitored changes in health and work across four surveys during March-December 2020. Outcomes described psychological distress, and mental and physical health. Linear mixed regression models examined associations between changes in health and experiences of work loss, and return to work, over time. Results: Losing work during the early pandemic stages was associated with long-term poorer mental health, which began to recover over time. Physical health deteriorated over time, greater for people not working at baseline. Being out of work was associated with poorer mental health, but better physical health. These effects were larger for people that had recently lost work than for people with sustained work loss, and retaining employment played a protective role. Conclusions: Work cessation during the pandemic led to poor health outcomes and had long-lasting effects. Returning to work benefits mental health but may reduce physical activity in the short-term. We encourage the provision of accessible mental health supports immediately following loss of work, and for people with prolonged work loss. Key messages: Remaining employed whilst not working partly ameliorates negative mental health impacts. Those experiencing persistent work loss, and the newly out-of-work, are most vulnerable to ill mental health.